Borderlands: The Institutional and Philosophical Consciousness of the Polish-Lithuanian Szlachta and the Korean Yangban in Early Modernity - Śleziak, Tomasz (International Journal of Korean Humanities and Social Sciences, 2024)
In this paper, the administration and dynamic cultures resulting from the disputed past, high ideals and challenges faced by the Polish-Lithuanian Commonwealth’s and Korea’s nobilities, along with their “Sarmatic” and Confucian frameworks are analyzed, with the evolving identities of Joseon’s and Rzeczpospolita’s Szlachta and Yangban social strata, their respective opponents, and the pragmatic realities that affected their status and activities, being within the center of inquiry.